The top 100 papers on prostate cancer-associated exosomes on social media: an altmetric study from the MENA region - Ansari, Nasim; Zaeri Basir, Faezeh; Mahami-Oskouei, Mina; Rashti, Roya; Ouchi, Ali (Frontiers in Oncology, 2025)
PurposeThis altmetric analysis aimed to identify and describe the top 100 papers on prostate cancer-associated exosomes in the Middle East and North Africa (MENA) region cited on social media.Design/methodology/approachAs an applied study with an altmetric approach, this research included all Science Citation Index (SCI) Expanded indexed papers on prostate cancer-associated exosomes in the MENA region during 1970–2023. Altmetric Attention Scores (AASs) were extracted from the Altmetric Explorer, and Excel and SPSS were used for data analysis.FindingTwitter ranked first in mentioning 73.55 of the top 100 studied papers. The highest score of mentions on Twitter equaled 187, and that of AAS was 516, which belonged to an original research article. However, the top paper in citation counts was a guideline (AAS = 116; citation count = 5,664 =). The Journal of Urology published most papers (n = 21), with total AAS = 1,094. Most papers were international collaborations (n = 82). There was no significant relationship between the AASs of papers and those of Web of Science (WoS) citation counts (R2 = 0.1284, p-value = 0.2054).Practical implicationsShowing a broad perspective on the research priorities and new directions in prostate cancer-associated exosomes, this study can be a guideline for finding main papers on diagnosing, treating, and preventing prostate cancer. It helps researchers, professionals, and policymakers in developing the use of social media in disseminating related information.OriginalityBy providing helpful information on prostate cancer-associated exosomes, this study can inform researchers and administrators of the state of research on the topic and consequent health promotion among the public.